2017
DOI: 10.1007/s40520-017-0735-6
|View full text |Cite
|
Sign up to set email alerts
|

Pros-IT CNR: an Italian prostate cancer monitoring project

Abstract: The study will provide information on patients' quality of life and its variations over time in relation to the treatments received for the prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…The Pros-IT CNR study design has been described elsewhere [ 8 ]. Briefly, the Pros-IT CNR is a multicenter, prospective study that aims to monitor the quality of life of a sample of Italian male patients 18 years and older who were diagnosed with biopsy-verified treatment-naïve prostate cancer after September 1, 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The Pros-IT CNR study design has been described elsewhere [ 8 ]. Briefly, the Pros-IT CNR is a multicenter, prospective study that aims to monitor the quality of life of a sample of Italian male patients 18 years and older who were diagnosed with biopsy-verified treatment-naïve prostate cancer after September 1, 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The Swedish Laparoscopic Prostatectomy Robot Open study [12,13] reported no differences in continence and sexual function for [14] reported no differences in urinary and sexual functions assessed at 12 months by the EPIC-26 questionnaire through phone interview on 2002 cases (1117 ORP, 885 RARP) treated in the period 2009-2012. Finally, a Korean study [15] at 7 academic centres with high-volume surgeons recruited 258 patients (41 ORP, 63 LRP, 105 RARP) from October 2014 to December 2015 and found a better recovery of sexual functions in the RARP and LRP groups, as measured by the EORTC QLQ-C30 questionnaire.…”
Section: Radical Prostatectomy In Pros-it Cnr Studymentioning
confidence: 99%
“…Such studies are potentially able to account for selection bias and provide more reproducible results [9]. Up to now, 6 populationbased projects [10][11][12][13][14][15] assessed the impact of surgical approach on perceptions of urinary, bowel, and sexual function and of general health-related quality of life (HRQoL) by validated patient-reported outcome measures (PROMs). However, these studies are not devoid of flaws, since they relied on long time span, generally including the learning phase of minimally invasive approaches.…”
Section: Introductionmentioning
confidence: 99%
“…A 44-year-old man received a kidney transplant from a braindead donor (DBD). The donor was 59 years old, had died from cerebral hemorrhage, his Kidney Donor Profile Index (KDPI) was 83%, Karpinsky's score was 3, and he had been a smoker with a past history of prostate cancer for which he was in regular follow-up (19). The surgeon described atheromatous plaques in the renal artery that were particularly evident at the confluence with the aorta and were partially removed before implantation.…”
Section: Case Report Casementioning
confidence: 99%